Reinforcement and contemporary evolutionary biology - Galvão, Olavo Faria (Brazilian Journal of Behavioral and Cognitive Therapy, 1999)
Reinforcement and contemporary evolutionary biology. The purpose of this article is to present to behavior analysts the justification and basic ideas of biobehavioral approach. Commonly, the evolution of scientific theories embroil surmounting dichotomies and demonstrating their consistency with analysis at different levels. The reinforcement theory, established on the operant respondent dichotomy, and the relationship between behavior analysis and neurophysiologic processes are reviewed through the biobehavioral approach, that is based in the unified principle of reinforcement, which is advanced after the interpretation of biochemical, anatomic and physiologic experimental evidences that the reinforcement involves the enhancement of synaptic efficacy and the formation of neural networks that correspond to the strengthening of environment behavior relationships.